Corporate Social Responsibility: Theories, Indexes, Standards and Certifications - Duque Orozco, Yenni Viviana; Cardona Acevedo, Marleny de la Milagrosa; Rendón Acevedo, Jaime Alberto (Cuadernos de Administración, 2013)
Corporate social responsibility (CSR), more than a fad in management and business reports, constitute a key exercise in the evolution of businesses that dates back a century. From the very concept, constant renewal is proposed that has enabled their maturation. This has also influenced on the forms of measurement, which has fallen onto a number of standards, guidelines, and methodologies that have contributed to understanding CSR but also come to mean the confusion with what should be the basic operating parameters. In the first part, this article takes stock of the concepts; in the second part, it examines the rules and guidelines; and in the third part, it concludes by proposing the need to build consensus against the rules and audits so that CSR is regulated in its minimum desirable by societies.